2019
DOI: 10.1042/bsr20181363
|View full text |Cite
|
Sign up to set email alerts
|

The Terminalia laxiflora modulates the neurotoxicity induced by fipronil in male albino rats

Abstract: The extensive use of fipronil (FPN) may trigger hazards to more than insects. The present investigation was carried out to evaluate the abrogating role of Terminalia laxiflora (TL) methanol extract (TLE) against the neurotoxic effects provoked by FPN. Fourty male albino rats were assigned into four equal groups. The first group served as control, the second one was orally administered FPN (10.5 mg/kg BW), the third group was given combination of FPN and TLE) (100 mg/kg BW), and the fourth one was orally given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
5
9
0
Order By: Relevance
“…It also altered the 5-HT tissue content. Previous studies showed that FPN dose-dependently changed the activity of various enzymes involved in oxidative stress and inflammation in the brain when chronically administered at the 5–30 mg/kg range of doses [ 8 , 9 , 11 , 12 , 38 ]. Thus, the dose of 10 mg/kg, considered as a moderate dose, profoundly alters the neurochemistry of monoamines, particularly DA and 5-HT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also altered the 5-HT tissue content. Previous studies showed that FPN dose-dependently changed the activity of various enzymes involved in oxidative stress and inflammation in the brain when chronically administered at the 5–30 mg/kg range of doses [ 8 , 9 , 11 , 12 , 38 ]. Thus, the dose of 10 mg/kg, considered as a moderate dose, profoundly alters the neurochemistry of monoamines, particularly DA and 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier reports suggest that FPN blocks chloride ion cellular uptake in invertebrates, leading to uncontrolled central nervous system (CNS) hyper-excitation by the blockage of GABA A receptors, convulsion, and cell death [ 6 , 7 ]. Although considered less toxic toward mammals, its absorption is rapid, and it easily crosses the blood brain barrier [ 8 ]. Recent alarming reports suggest that chronic FPN in rodents at 30 but not 10 mg/kg by daily oral gavage causes memory impairment in parts associated with the modulation of the GABAergic system [ 9 ] and the deposition of amyloid plaques [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sample was homogenised using liquid nitrogen, and the total RNA was extracted using the Qiagen RNeasy Mini Kit according to the manufacturer's instructions. Both the concentration and purity of the isolated RNA were tested by NanoDrop . The RT‐PCR was performed using the RevertAid First Strand cDNA Synthesis Kit according to the guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…After the concentration and purity of RNA were confirmed, 1000 ng purified RNA was used to synthesize 20 μl cDNA, using a Revert aid™ first-strand cDNA synthesis kit (Fermentas, Germany) according to the manufacturer's instructions (Khalaf et al 2019a). Relative quantitative assessment of mRNA transcript amplification for each gene was performed relative to betaactin (ACTB) by a fluorescence-based real-time detection method with a fluorescent SYBR Green dye (Thermo Scientific) (Khalaf et al 2019b). The sequences of all the primer sets used are listed in Table 1.…”
Section: Assessment Of Liver Function and Antioxidant Activitymentioning
confidence: 99%